Menganalisis Tingkat Kesehatan Bank Umum Syariah Di Indonesia Dengan Menggunakan Metode Camel Periode 2014-2018 - HS, Sufyati; Pristiani, Novita (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
PurposeThe purpose of this study is to determine the level of financial health at Islamic Commercial Banks in MethodologyIndonesia using the CAMEL method which consists of Capital, Assets, Management, Earning and Liquidity in the period 2014-2018.The type of data used in this study is secondary data in the form of financial at PT. Bank Syariah Mandiri and PT. BNI Syariah Bank. Findings . Based on the results of an analysis of the level of soundness of a bank using the CAMEL Method in terms of calculating known ratios from the analysis of Capital, Capital, Asset (Earning Quality), Earning (Rentability) of the two Sharia Commercial Banks in 2014-2018 are all in the second healthy predicate except for the Management (Liquid) and Liquidity (Liquidity) factors of the two Sharia Commercial Banks which started in 2014-2018 all are in reasonably healthy condition. Suggestion For customers and potential investors, these two Islamic Commercial Banks can be used as an option to invest their funds because seen from all aspects of the weight of CAMEL, the average is in a healthy condition.